Psychology : why we smile, strive, and sing - Rubini, Julie (Inquire and investigate., 2020)
Presents the history of human psychology and how human behavior is tied to the brain. Highlights information about the teenage brain and how other factors like our environment, the people around us, and being in a group can influence our psychology. Includes color illustrations, diagrams, experiments, a timeline, a glossary, and additional resources.